Bacterial community dynamics following antibiotic exposure in a trematode parasite. Issue 5 (April 2022) - Jorge, Fátima; Froissard, Céline; Dheilly, Nolwenn M.; Poulin, Robert
Graphical abstract: Highlights: Parasite microbiomes can affect multiple facets of host-parasite interactions. We develop an experimental protocol to manipulate bacterial communities in trematodes. We show that indirect antibiotic exposure alters the structure of trematode bacterial communities. Different antibiotics had different impacts on bacterial diversity or abundance. Over time post-exposure, bacterial communities in trematodes gradually changed toward a new state. Abstract: Parasites harbour rich microbial communities that may play a role in host-parasite interactions, from influencing the parasite's infectivity to modulating its virulence. Experimental manipulation of a parasite's microbes would be essential, however, in order to establish their causal role. Here, we tested whether indirect exposure of a trematode parasite within its snail intermediate host to a variety of antibiotics could alter its bacterial community. Based on sequencing the prokaryotic 16S ssrRNA gene, we characterised and compared the bacterial community of the trematode Philophthalmus attenuatus before, shortly after, and weeks after exposure to different antibiotics (penicillin, colistin, gentamicin) with distinct activity spectra. Our findings revealed that indirectly treating the parasites by exposing their snail host to antibiotics resulted in changes to their bacterial communities, measured as their diversity, taxonomic composition, and/or the relative abundance of certain taxa. However, alterations to the parasite's bacterial community were not always as predicted from the activity spectrum of the antibiotic used. Furthermore, the bacterial communities of the parasites followed significantly divergent trajectories in the days post-exposure to antibiotics, but later converged toward a new state, i.e. a new bacterial community structure different from that pre-exposure. Our results confirm that a trematode's microbial community can be experimentally altered by antibiotic exposure while within its snail host, with the dynamic nature of the bacterial assemblage driving it to a new state over time after the perturbation. This research opens new possibilities for future experimental investigations of the functional roles of microbes in host-parasite interactions.